2008
DOI: 10.1007/s11064-008-9675-z
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Protects Dopaminergic Neuron Against LPS Induced Neurotoxicity in Primary Rat Neuron/Glia Culture

Abstract: Using primary rat mesencephalic neuron-glia cultures as an in vitro model of Parkinson's disease (PD), we tested the effect of curcumin, a natural dietary pigment with well-known anti-inflammation effects, on dopaminergic (DA) degeneration. Curcumin pretreatment mitigated LPS-induced DA neurotoxicity in a concentration-dependent manner and curcumin post-treatment also showed protective effect. Microglia depletion abolished this protective effect of curcumin, indicating that microglia play an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 49 publications
4
47
0
Order By: Relevance
“…Careful targeting of these cells could have therapeutic benefits for several types of trauma and disease specific to the central nervous system. Previous in vivo or in vitro studies have revealed that drugs such as tetracyclines [30], histone deacetylase inhibitors [31], naloxone [32], dextromethorphan [33], curcumin [28] and several polyphenolic plant-derived flavonoids [27] afford neuroprotection through modulating microglial cells. Of course, we should not seriously hamper their critical role in host defense and their neuroregenerative properties when modulating the deleterious aspects of activated microglia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Careful targeting of these cells could have therapeutic benefits for several types of trauma and disease specific to the central nervous system. Previous in vivo or in vitro studies have revealed that drugs such as tetracyclines [30], histone deacetylase inhibitors [31], naloxone [32], dextromethorphan [33], curcumin [28] and several polyphenolic plant-derived flavonoids [27] afford neuroprotection through modulating microglial cells. Of course, we should not seriously hamper their critical role in host defense and their neuroregenerative properties when modulating the deleterious aspects of activated microglia.…”
Section: Discussionmentioning
confidence: 99%
“…It's also an important target of several anti-inflammatory drugs [27,28]. Recent experiment evidence demonstrates that Sal B can suppress NF-jB activation in endothelial cell [16,18] and mesangial cell [19].…”
Section: Sal B Inhibits Lps-induced Nf-jb Activation In Microglial Cellsmentioning
confidence: 99%
“…LPS stimulation enhanced the level of ADAM17 and TNF-α secreted from oral keratinocytes, although differences in the level of enhancement existed with respect to the origin, concentration and time of LPS exposure to the cells. Previous studies report that the signaling pathway of P. gingivalis LPS differs from that of E. coli LPS in cells (22), which leads to differential immune responses with respect to mRNA expression levels and the time course of each cytokine (5). Thus, differences in TNF-α levels released from cells following E.…”
Section: Effect Of Sirna Targeting On Adam17 Expression In Hoksmentioning
confidence: 99%
“…In an experimental allergic encephalomyelitis (EAE) mouse model of MS, curcumin inhibited EAE development by attenuating microglia activation and IL-12 production as well as Th1 cell differentiation (Natarajan and Bright 2002). Curcumin also has shown protective effects against LPS-induced DA neuron cell death in mixed rat neuron-glial cell cultures which were mediated by inhibition of the production of proinflammatory factors in microglia (Yang, Zhang et al 2008). Taken together, the neuroprotective results from these three natural plant products suggest an interesting possibility for PD therapeutics.…”
Section: Sinomenine Luteolin and Curcumin As Treatments For Parkinsomentioning
confidence: 99%